Mendelian randomization suggests a potential causal effect of eosinophil count on influenza vaccination responsiveness. Issue 1 (30th December 2022) - Chen, Hongwei; Zhang, Haoyang; Wen, Simin; Xiu, Xuehao; You, Danming; Zhao, Huiying; Wang, Dayan; Yang, Yuedong; Shu, Yuelong
Abstract: Currently, the clinical factors affecting immune responses to influenza vaccines have not been systematically explored. The mechanism of low responsiveness to influenza vaccination (LRIV) is complicated and not thoroughly elucidated. Thus, we integrate our in‐house genome‐wide association studies (GWAS) analysis result of LRIV ( N  = 111, Ncase [Low Responders] = 34, Ncontrol [Responders] = 77) with the GWAS summary of 10 blood‐based biomarkers (sample size ranging from 62 076−108 794) deposited in BioBank Japan (BBJ) to comprehensively explore the shared genetics between LRIV and blood‐based biomarkers to investigate the causal relationships between blood‐based biomarkers and LRIV by Mendelian randomization (MR). The applications of four MR approaches (inverse‐variance‐weighted [IVW], weighted median, weighted mode, and generalized summary‐data‐based MR [GSMR]) suggested that the genetically instrumented LRIV was associated with decreased eosinophil count ( β  = −5.517 to −4.422, p  = 0.004−0.039). Finally, we conclude that the low level of eosinophil count is a suggestive risk factor for LRIV.